Multipod structures of lamellae‐forming diblock copolymers in three‐dimensional confinement spaces: Experimental observation and computer simulation. Issue 17 (8th May 2016) - Higuchi, Takeshi; Pinna, Marco; Zvelindovsky, Andrei V.; Jinnai, Hiroshi; Yabu, Hiroshi
ABSTRACT: The three‐dimensional (3D) confinement effect on the microphase‐separated structure of a diblock copolymer was investigated both experimentally and computationally. Block copolymer nanoparticles were prepared by adding a poor solvent into a block copolymer solution and subsequently evaporating the good solvent. The 3D structures of the nanoparticles were quantitatively determined with transmission electron microtomography (TEMT). TEMT observations revealed that various complex structures, including tennis‐ball, mushroom‐like, and multipod structures, were formed in the 3D confinement. Detailed structural analysis, showed that one block of the diblock copolymer slightly prefers to segregate into the particle surface compared with the other block. The observed structures were further elaborated using cell dynamics computer simulation. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1702–1709 Abstract : The three‐dimensional (3D) confinement effect on the microphase‐separated structure of a diblock copolymer was investigated both experimentally and theoretically. In conjunction with the experiment, the morphologies were computationally simulated by using parameters to match the actual 3D structures obtained with transmission electron microtomography. The simulated structures appear in good agreement with the experimental results.